2012
DOI: 10.1038/bjc.2012.539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sorafenib combined with cytostatic agents on hepatoblastoma cell lines and xenografts

Abstract: Background:Sorafenib has recently been shown to reduce tumour growth in hepatoblastoma (HB) xenografts. The effect of a combined administration with cytostatic agents was now investigated.Methods:Cell viability after treatment with sorafenib and different cytostatic agents was evaluated in two HB cell lines (HUH6 and HepT1) using MTT assay. ERK signalling was investigated by western blot, NOXA expression by rt-PCR, and formation of DNA adducts using immunocytology. NMRI mice bearing subcutaneous HUH6-derived t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 20 publications
(31 reference statements)
1
16
1
Order By: Relevance
“…Growth inhibition of 50% was assessed at nearly the same concentrations found in the HB cell lines HUH6 and HepT1. Western blot analyses confirmed potent inhibition of the Raf/MEK/ ERK signaling pathway in HC-AFW1 cells as well as in tumor xenografts, which is known to be the key mechanism of inhibiting cell proliferation by sorafenib, already described for the aHCC cell lines PLC/PRF/5, Huh7 as well as for HB cell lines [15,16,22].…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Growth inhibition of 50% was assessed at nearly the same concentrations found in the HB cell lines HUH6 and HepT1. Western blot analyses confirmed potent inhibition of the Raf/MEK/ ERK signaling pathway in HC-AFW1 cells as well as in tumor xenografts, which is known to be the key mechanism of inhibiting cell proliferation by sorafenib, already described for the aHCC cell lines PLC/PRF/5, Huh7 as well as for HB cell lines [15,16,22].…”
Section: Discussionmentioning
confidence: 51%
“…To evaluate tumor response, tissue histology and mean vascular density (MDV) were performed as previously described [15,16]. Capillaries were revealed by CD31-immunostaining using the monoclonal rat anti-mouse CD31 antibody (1:20; Dianova, Hamburg, Germany) and the Avidin-biotin-peroxidase-complex (Linaris, Wertheim, Germany) according to manufacturer's protocol.…”
Section: Vascularizationmentioning
confidence: 99%
See 2 more Smart Citations
“…ERK and its upstream kinase MEK localize to the extraluminal face of autophagosomes and ERK phosphorylation is upregulated by lipidation of autophagic protein LC3 (32). It has been shown that the treatment of various types of cancer, such as ovarian carcinoma (33), melanoma (34), and liver cancer cells (35) with CDDP caused ERK activation and cell death, and this latter effect was potentiated by ERK inhibitors, indicating that ERKs behave as survival-inducing kinases in these cells. Consistent with those results, our study has shown that CDDP caused ERK activation in Saos-2 cells.…”
Section: Discussionmentioning
confidence: 99%